The Correlation Between Low Body Mass Index (underweight) With Bone Strength On Eldery Women - Shafira Dwi Resnasari (Saintika Medika, 2020)
Background : Osteoporosis is a degenerative disease that often happend at women in elderly age with low body mass index. Standard examination for osteoporosis is bone density examination also known as Bone Mineral Density (BMD). This tool can interpret the patient’s bone strengthObjective : This research aims to identify the correlation between low body mass index (underweight) with bone strength on elderly women.Method : This is an observational analytic research which used cross sectional design. The sample consist of 65 respondents. The data were analyzed by using Chi-square test.Result : The result shows a large group of respondents aged 60-65 years old with a percentage of 18.5% suffers from osteopenia and a percentage of 47.7% suffers from osteoporosis. Furthermore, a percentage of 13.8% in underweight respondents suffers from osteopenia and a percentage of 47.7 % suffers from osteoporosis.Conclusion : This research proves that there is a correlation between low body mass index with bone strength on elderly women with P-value amounting to 0.022 (P < 0.05) for variable relationships between elderly age with bone strength and P-value of 0.002 (P < 0.05) for variable relationships between low body mass index with bone strength.Keyword : Osteoporosis, Body Mass Index, Bone Density